Needle Puncture Injury Causes Acute and Long-Term Mechanical Deficiency in a Mouse Model of Intervertebral Disc Degeneration - Martin, John T. (J Orthop Res, 2013)
Low back pain is a significant socioeconomic burden and intervertebral disc degeneration has been implicated as a cause. A reliable animal model of disc degeneration is necessary to evaluate therapeutics, and functional metrics are essential to quantify their benefit. To this end, needle puncture injuries were created in the caudal intervertebral discs of mice to induce disc degeneration. Compression, torsion, and creep mechanics were assessed both immediately and after eight weeks to distinguish between the effects of injury and the subsequent reparative or degenerative response. Two needle sizes (29 and 26 gauge) were used to determine injury size-dependence. Compressive stiffness (62%), torsional stiffness (60%), and early damping stiffness (84%) decreased immediately after injury with the large needle (26G). These mechanical properties did not change over time despite structural and compositional changes. At 8 weeks following large needle injury, disc height decreased (37%), nucleus pulposus (NP) glycosaminoglycan content decreased (41%), and NP collagen content increased (45%). The small needle size had no significant effect on mechanics and did not initiate degenerative changes in structure and composition. Thus, the injection of therapeutics into the NP with a minimal needle size may limit damage due to the needle insertion. These findings, along with the wide commercial availability of mouse-specific biological probes, indicate that the mouse caudal disc model can be a powerful tool for investigating disc degeneration and therapy.